Early maternal deprivation induces gender-dependent changes on the expression of hippocampal CB(1) and CB(2) cannabinoid receptors of neonatal rats. - Suárez-Pérez, Juan; Llorente, Ricardo; Romero-Zerbo, Silvana Yanina; Mateos, Beatriz; Bermúdez Silva, Francisco Javier; Rodriguez-de-Fonseca, Fernando; Paz Viveros, Maria (Wiley, 2009)
Early maternal deprivation (MD) in rats (24 h, postnatal day 9–10) is a model for neurodevelopmental stress. There are some data proving that MD affects the endocannabinoid system (ECS) in a gender-dependent manner, and that these changes may account for the proposed schizophrenia-like phenotype of MD rats. The impact of MD on cannabinoid receptor distribution in the hippocampus is unknown. The aim of this study is to evaluate the expression of CB1 and CB2 receptors in diverse relevant subregions (DG, CA1, and CA3) of the hippocampus in 13-day-old rats by immunohistochemistry and densitometry. MD induced a significant decrease in CB1 immunoreactivity (more marked in males than in females), which was mainly associated with fibers in the strata pyramidale and radiatum of CA1 and in the strata oriens, pyramidale, and radiatum of CA3. In contrast, MD males and females showed a significant increase in CB2 immunoreactivity in the three hippocampal areas analyzed that was detected in neuropil and puncta in the stratum oriens of CA1 and CA3, and in the polymorphic cell layer of the dentate gyrus. A marked sex dimorphism was observed in CA3, with females exhibiting higher CB1 immunoreactivity than males, and in dentate gyrus, with females exhibiting lower CB2 immunoreactivity than males. These results point to a clear association between developmental stress and dysregulation of the ECS. The present MD procedure may provide an interesting experimental model to further address the role of the ECS in neurodevelopmental mental illnesses such as schizophrenia. © 2008 Wiley-Liss, Inc.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/13858
Keywords: Hipocampo (Cerebro) - Modelos animales; Carencia materna - Modelos animales; CB2 cannabinoid receptors; CB1 cannabinoid receptors; Neonatal rat; Maternal deprivation; Animal model of schizophrenia; Hippocampus